2007
DOI: 10.1029/2006jb004882
|View full text |Cite
|
Sign up to set email alerts
|

Signal and noise in Gravity Recovery and Climate Experiment (GRACE) observed surface mass variations

Abstract: [1] The Gravity Recovery and Climate Experiment (GRACE) product used for this study consists of 43 monthly potential coefficient sets released by the GRACE science team which are used to generate surface mass thickness grids expressed as equivalent water heights (EQWHs). We optimized both the smoothing radius and the level of approximation by empirical orthogonal functions (EOFs) and found that 6.25°a nd three modes are able to describe more than 73.5% of the variance. The EQWHs obtained by the EOF method desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 18 publications
(29 reference statements)
3
67
0
Order By: Relevance
“…Information on individual storage components will be extremely valuable towards improving hydrological models efficiently for individual process descriptions. Progress in signal separation requires combined analyses using new observations, modelling, inversion techniques (e.g., Ramillien et al 2004) and advanced statistical methods for identifying dominant and significant signal components (e.g., Schrama et al 2007;Schmidt et al 2008a). …”
Section: • Error Estimates For Grace Datamentioning
confidence: 99%
“…Information on individual storage components will be extremely valuable towards improving hydrological models efficiently for individual process descriptions. Progress in signal separation requires combined analyses using new observations, modelling, inversion techniques (e.g., Ramillien et al 2004) and advanced statistical methods for identifying dominant and significant signal components (e.g., Schrama et al 2007;Schmidt et al 2008a). …”
Section: • Error Estimates For Grace Datamentioning
confidence: 99%
“…One category is empirical that does not use any other information (Swenson and Wahr 2006;Chambers 2006;Chen et al 2007;Schrama et al 2007;Wouters and Schrama 2007;Davis et al 2008). The other category makes use of the error variance-covariance matrix of the SCs, but also requires a priori signal covariance information (Kusche 2007;Klees et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chambers (2006) and Chen et al (2007) followed the principle of Swenson and Wahr (2006), but chose to fit all the even/odd SCs of the same order to be decorrelated using a polynomial. Schrama et al (2007) and Wouters and Schrama (2007) made use of empirical orthogonal functions (EOFs). Their difference is that Schrama et al (2007) performed the computation in the spatial domain, and Wouters and Schrama (2007) performed the computation in the spherical harmonic domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aliasing and the modelling errors are responsible for the spurious meridional undulations present in the GRACE monthly grids and known as north-south striping. They are associated to spherical harmonics order 15 and its multiples (Swenson & Wahr, 2006a;Schrama et al, 2007;Seo et al, 2008). Thompson et al (2004) showed that the degree error increased by factors ~ 20 due to atmospheric aliasing, ~ 10 due to the ocean model, and ~ 3 due to continental hydrology model.…”
Section: The Problem Of Aliasingmentioning
confidence: 99%